2023
DOI: 10.5535/arm.22108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrathecal Baclofen Pump on Scoliosis in Children With Cerebral Palsy: A Meta-Analysis

Abstract: Cerebral palsy (CP) refers to a disorder of movement and posture with "non-progressive, but often changing motor impairment syndromes secondary to lesions or anomalies of the brain, arising in the early stages of its development [1,2]." The three subtypes of CP are named after the types of motor dysfunction: spastic, dyskinetic, and ataxic [3]. Spastic CP is observed in 70%-80% of patients with CP [4]. Spasticity has long affected patients' quality of life, hampering their basic activities of daily living [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…25,26 Lumbosacral VDR has the potential to address the relative contraindications of ITBP including scoliosis, epilepsy, low weight, and an age < 4 years. 10,12 The prevalence of scoliosis and epilepsy in our cohort was 71% and 57%, respectively. We observed no increase in seizure frequency or worsening of spinal deformity associated with the VDR in the follow-up period, but long-term follow-up is mandatory in this patient population.…”
Section: Indicationsmentioning
confidence: 77%
See 1 more Smart Citation
“…25,26 Lumbosacral VDR has the potential to address the relative contraindications of ITBP including scoliosis, epilepsy, low weight, and an age < 4 years. 10,12 The prevalence of scoliosis and epilepsy in our cohort was 71% and 57%, respectively. We observed no increase in seizure frequency or worsening of spinal deformity associated with the VDR in the follow-up period, but long-term follow-up is mandatory in this patient population.…”
Section: Indicationsmentioning
confidence: 77%
“…11 A recent meta-analysis demonstrated that ITBP insertion accelerates the annual Cobb angle progression in children with CP. 12 Some practitioners consider the ITBP to be relatively contraindicated in patients with epilepsy given concerns about increasing seizure frequency. A recent meta-analysis noted a 38% pooled prevalence of epilepsy in CP.…”
mentioning
confidence: 99%
“…ITBP demonstrates reduction in upper extremity mAS scores by 0.8 to 1.8 compared with 1.75 to 2.5 in our cohort [26,27]. Moreover, ITBP is relatively contraindicated in patient populations with low weight, epilepsy, scoliosis, and age less than four and cervical VDR is not similarly constrained [28,29]. This study included patients aged 7-34 and there was no cognitive threshold imposed.…”
Section: Indications and Considerationsmentioning
confidence: 92%
“…However, the impact on scoliosis after ITB pump implantation has been controversial in children with CP with further scoliosis progression [18][19][20] vs. no significant difference [21,22]. In their study published in current issue of Annals of Rehabilitation Medicine, Lee et al [23] performed a systematic review and meta-analysis www.e-arm.org which showed that ITB pump implantation accelerates annual Cobb's angle progression in children with CP. Patients with ITB pump implantation showed a faster rate of scoliosis progression probably due to paraspinal muscle hypotonia, although patients with no ITB pump implantation also showed aggravation of scoliosis.…”
mentioning
confidence: 99%